Intelligent Decision Technologies 2017 Proceedings of the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT 2017) - Part II - Czarnowski, Ireneusz; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The volume presents a collection of peer-reviewed articles from the 9th KES International Conference on Intelligent Decision Technologies (KES-IDT-17), held in Vilamoura, Algarve, Portugal on 21-23 June 2017. The conference addressed critical areas of computer science, as well as promoting knowledge transfer and the generation of new ideas in the field of intelligent decision making, project management and data analysis. The range of topics addressed includes methods of classification, prediction, data analysis, decision support, modeling, social media and many more in such diverse areas as finance, linguistics, management and transportation.
A Development of Classification Model for Smartphone Addiction Recognition System Based on Smartphone Usage Data -- Complex Object Recognition Based on Multi-shape Invariant Radon Transform -- Genetic Algorithms Based Resampling for the Classification of Unbalanced Datasets -- Analysis of Multiple Classifiers Performance for Discretized Data in Authorship Attribution -- Speaker Identification in Noisy Conditions Using Short Sequences of Speech Frames -- Decision-Controlled Digitization Architecture for Internet of Things and Microservices -- Digital Enterprise Architecture Management in Tourism - State of the Art and Future Directions -- Building Fuzzy Variance Gamma Option Pricing Models With Jump Levy Process -- Evolutionary Regressor Selection in ARIMA Model for Stock Price Time Series Forecasting -- Applying Domain Knowledge for Data Quality Assessment in Dermatology -- A Data Analytics Framework for Business in Small and Medium-Sized Organizations -- Visual Analysis of Eye Movement Data with Fixation Distance Plots -- Which Symbols, Features, and Regions Are Visually Attended in Metro Maps? -- Measurements of Contrast Detection Thresholds for Peripheral Vision Using Non-flashing Stimuli -- Social Stream Clustering to Improve Events Extraction -- A New Social Recommender System Based on Link Prediction Across Heterogeneous Networks -- Social Market: Stock Market and Twitter Correlation.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence